Green hydrogen production by an improved photoelectrochemical process with Ga-doped ZnO photoanodes on stainless steel substrates☆ - Ayca, Sumeyya; Dincer, Ibrahim (ELSEVIER SCIENCE SA, 2026)
This study analyzes hydrogen production using photoelectrochemical (PEC) water splitting methods for Gadoped ZnO electrodes coated on stainless steel. Physical electrochemistry, electrochemical impedance, hydrogen production, X-ray diffraction (XRD), and scanning electron microscopy (SEM) analyses are performed on uncoated, undoped ZnO-coated, and Ga-doped ZnO-coated electrodes. The parameters of the best-coated electrode obtained by chronoamperometry (CA) analysis are as follows: the electrode is immersed in a dipcoating bath for 4 s, is coated five times, and has a doping ratio of 1%. The Tafel slope obtained from the Tafel graph of the 1% Ga-doped ZnO electrode is 0.15 V/dec, and the change in current density is 1.05 x 10- 7 A/ cm2. According to the electrochemical impedance spectroscopy (EIS) data, the solution resistance (Rs), polarization resistance (Rp), and constant phase element (CPE) of the 1% Ga-doped ZnO electrode are 0.4862 Omega & sdot;cm2, 0.0785 Omega & sdot;cm2, and 2.031 x 10-3 Omega- 1 & sdot;s & sdot;cm- 2, respectively. The slope value obtained from the Mott-Schottky graph is also 3.45 x 10-4. The hydrogen production rate obtained from CA analysis over a half-hour period is 6 ml/cm2. The energy efficiency is 2.3%, the exergy efficiency is 2.36%, and the applied bias photon-to-current efficiency (ABPE) is 0.75%. This study demonstrates higher hydrogen evolution reaction (HER) activity and overall efficiency than comparable studies in the literature. This study is the first in the literature to illustrate the dip-coating of Ga-doped ZnO electrodes onto stainless steel, the optimization of coating number and duration parameters, and the reporting of direct hydrogen production quantities. Thus, the study fills a gap in the literature in terms of both methodological innovation and performance, offering an applicable and scalable approach for sustainable hydrogen production.
Keywords: Ga-doped ZnO; Nanoparticles; Photoanodes; Photoelectrochemical water splitting; Dip-coating technique; Green hydrogen production; Efficiency; Sustainable development; PERFORMANCE; Materials Science; Physics